A superior preparation method for daidzein-hydroxypropyl-β-cyclodextrin complexes with improved solubility and dissolution: Supercritical fluid process - Pan Hao; Wang Han-Bing; Yu Yi-Bin; Cheng Bing-Chao; Wang Xiao-Yu; Li Ying (Acta Pharmaceutica)
Advantages of the supercritical fluid (SCF) process compared to the conventional solution stirring method (CSSM) in the preparation of daidzein-hydroxypropyl-β-cyclodextrin (HPβCD) complexes were investigated. Formation of daidzein/ HPβCD inclusion complexes was confirmed by Fourier transformed-infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Particle size, inclusion yield, drug solubility and dissolution of daidzein/HPβCD complexes were evaluated. Compared to CSSM, the SCF process resulted in higher inclusion yield and higher solubility. Also, extended dissolution of daidzein from the SCF processed HPβCD inclusion complexes was observed, with only 22.94 % released in 45 min, compared to its rapid release from those prepared by CSSM, with 98.25 % drug release in 15 min. This extended release of daidzein from SCF prepared inclusion complexes was necessary to avoid drug precipitation and improve drug solubilisation in the gastrointestinal tract. The results showed that the SCF process is a superior preparation method for daidzein-hydroxypropyl-β-cyclodextrin complexes.